Green Port Strategies for Indonesian Maritime Logistics: A Systematic Review of Mining Barging and General Cargo - Samuel Darwisman; Marcellus Jayawibawa; Handy Bugiman; Ahmad Fajar Asrori; Agus Dian Hermawan; Zaenal Abidin (Dinasti International Journal of Education Management and Social Science, 2025)
Indonesia's maritime logistics, particularly its vital mining barging and general cargo sectors, face a critical tension between economic growth and environmental sustainability. While green port strategies are a national priority, a holistic synthesis connecting global principles to Indonesia’s unique archipelagic context is absent. This study bridges that gap via a systematic literature review, adhering to PRISMA guidelines. A rigorous analysis of 37 high-quality articles (2015-2025), appraised via the CASP checklist, reveals a persistent "policy-practice gap" and an "implementation chasm." Findings confirm that while implementation is driven by regulatory compliance, it is severely constrained by prohibitive capital investment, fragmented governance, and challenging economic feasibility. In response, this review delivers the first integrated synthesis for these non-containerized sectors, proposing a novel conceptual framework that models the interplay of drivers and barriers. It also establishes a targeted research agenda focused on context-specific techno-economic models. This study provides a foundational, evidence-based roadmap for Indonesian stakeholders to foster a resilient and genuinely sustainable maritime logistics ecosystem.